Glycine Betaine and Proline Production in Eucalyptus Plant under NaCl Harassing Environment - Qureshi, T. M.; Bano, A.; Ashraf, M. Y. (The Nucleus, 2015)
An investigation has been carried out to study the production of Proline and Betaine by applying Abscisic acid (ABA) treatment under NaCl and water stressed conditions. The seeds of four provenances of Eucalyptus camaldulesnis were obtained from the University of Agriculture, Faisalabad (Provenance I), Punjab Forest Research Institute, Faisalabad (Provenance II), Biosaline Research Station-I, Lahore (Provenance III) and Bio-saline Research Station-II of Nuclear Institute for Agriculture and Biology (NIAB), Faisalabad (Provenance 1V). It was observed that Proline and Betaine accumulation increased significantly in all the provenances with increase in drought or salt stress, ABA alone and in combination with drought. Provenance II and III species remained successful in maintaining higher Proline and Betaine accumulation as compared to Provenances I and IV. From the results it can be concluded that ABA treatment remains successful in enhancing Proline and Betaine production and maintaining the physiological parameters necessary to enhance plant growth both under salt and in combination with drought condition.